Cook County manual of emergency procedures - Simon, Robert R. [ (Robert Rutha)] (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"The purpose of this book is to provide the physician with an easy-to-use, step-by-step approach to procedures performed in an emergency department. Each procedure is divided into Preparatory Steps and Procedural Steps. Preparatory Steps discuss positioning the patient, prepping the patient, and other steps. Procedural Steps describe the actual procedure in detail, supplying ample illustrations of key points"--Provided by publisher.